Faktor-Faktor Internal Keuangan sebagai Determinan Nilai Perusahaan - Inastasya Shafira; Najmudin Najmudin; Intan Shaferi (Faculty of Economics and Business, Universitas Stikubank, 2022)
The purpose of this study is to analyze the effect of profitability, leverage, liquidity, activity, and investment decisions on firm value. The population of this study is all consumer goods companies listed on the Indonesia Stock Exchange. The technique in determining the sample used a purposive sampling method and obtained as many as 34 companies as research samples. The data in this study were tested using multiple linear regression analysis techniques with ordinary least squares. The findings of this study provide an indication that there is a significant positive effect on firm value from the determinants of profitability, leverage, financial activity, and investment decisions. Meanwhile, the determinant of liquidity has no influence on firm value.